2019
DOI: 10.1080/23273798.2019.1602733
|View full text |Cite
|
Sign up to set email alerts
|

Passives are not hard to interpret but hard to remember: evidence from online and offline studies

Abstract: Passives are not hard to interpret but hard to remember:Evidence from online and offline studies.Passive sentences are considered more difficult to comprehend than active sentences.Previous online-only studies cast doubt on this generalization. The current paper directly compares online and offline processing of passivization and manipulates verb type: state vs. event. Stative passives are temporarily ambiguous (adjectival vs. verbal), eventive passives are not (always verbal). Across 4 experiments (self-paced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 83 publications
8
28
0
2
Order By: Relevance
“…In contrast, our results favour models which hold that the HPM generates veridical representations for noncanonical sentences as well, and which attribute misinterpetation effects to postinterpretive processes that operate on those representations and that possibly have very different sources. As shown here and in other studies (Bader & Meng, 2018; Christianson et al, 2010; Paolazzi et al, 2019), such processes are strongly dependent on situational variables, such as demands of the task used to assess comprehension. Assuming that the processes responsible for misinterpretation errors operate after a correct syntactic representation has been computed by the HPM is also in line with recent research into lingering effects observed for garden-path sentences such as NP/S ambiguities.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In contrast, our results favour models which hold that the HPM generates veridical representations for noncanonical sentences as well, and which attribute misinterpetation effects to postinterpretive processes that operate on those representations and that possibly have very different sources. As shown here and in other studies (Bader & Meng, 2018; Christianson et al, 2010; Paolazzi et al, 2019), such processes are strongly dependent on situational variables, such as demands of the task used to assess comprehension. Assuming that the processes responsible for misinterpretation errors operate after a correct syntactic representation has been computed by the HPM is also in line with recent research into lingering effects observed for garden-path sentences such as NP/S ambiguities.…”
Section: Discussionsupporting
confidence: 75%
“…A similar account which also holds postinterpretive processes responsible for the misinterpretation of unambiguous noncanonical sentences has been proposed by Paolazzi et al (2019). This study reports the results of four experiments that examined the processing of English active and passive sentences combining an online method to tap processing difficulty (self-paced reading) and an offline method to assess interpretation (yes/no comprehension questions).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Although we believe that checking participants' interpretations of agreement attraction sentences is crucial to disentangling the encoding-and retrieval-based accounts, there is a significant caveat to using comprehension questions: One cannot be certain that the given answer matches the thematic relations computed during the online processing of the sentence (see also Schlueter et al, 2019). Bader and Meng (2018) have recently argued that answers to comprehension questions may be the result of what Caplan and Waters (1999) call post-interpretive processing (see also Paolazzi, Grillo, Alexiadou, & Santi, 2019). Caplan and Waters argue that the parser generates a syntactic structure and assigns meaning to the sentence online (interpretive processing), but that afterwards additional processes come into play whose output does not always match the online interpretation.…”
Section: Discussionmentioning
confidence: 99%